More than meets the eye - Yuen, Jia Jun (Nanyang Technological University, 2021)
More Than Meets The Eye explores the dog-eat-dog society where people often make superficial judgements, landing themselves in difficult situations. The animalistic trait of 'camouflage' is used as a metaphor for the notion of prey vs predator, which mirrors the societal structure of human life. The motifs of prey and predator were curated through the basis of similarity, creating an illusory experience that demonstrates the unassumingly contradictory nature of these similar patterns. The patterns seem to blend together uniformly from a distance, but closer inspection reveals each animal’s true form. The stripes of a tiger and the stripes of a zebra camouflaged among each other, yet their purposes are different — one uses it to hide, while the other uses it to hunt.